166k views
4 votes
Solve the following radical equation
√4z²-13z+9+3=3z

User George Lee
by
7.1k points

1 Answer

4 votes

To solve the radical equation √4z²-13z+9+3=3z, we need to get rid of the radical sign in order to isolate the variable.

First, we can add 9 to both sides to get:

√4z²-13z+12=3z+9

Then we can square both sides of the equation:

4z²-13z+12 = 9z²+27z+81

Now, we can rearrange the equation to get:

9z²-40z+69 = 0

Now we can use the quadratic formula to find the solutions for z:

z = (40 ± √(40²-4969)) / 2*9

z = (40 ± √(1600-2772)) / 18

z = (40 ± √(-1172)) / 18

Since the square root of a negative number is an imaginary number, this equation has no real solutions, which means that there are no values of z that will make the equation true.

So the radical equation √4z²-13z+9+3=3z doesn't have any solution.

User Gaurav Deochakke
by
7.2k points